(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this study was to study the species and prevalence GINs and detect the efficacy and resistance of some anthelmintics in local goats in northern Iraq. A total of 180 local goats originating from 25 goat farms were examined. As a result twelve species of these worms have been diagnosed, with a percentage of infection 64.44%, The Marshallagia spp. had the highest incidence 53.4%. The efficacy of anthelmintic drugs in the 3rd week after treatment for each the Ivermectin, A sativum, C colocynthis and O oil, reached to 95.3, 62.3, 92 and 31.2% respectively, and the study noted that there is resistance to some of these therapies by some types of worms.